The Linux essentials - Pezet, Don; Spurgin, Aubri (Packt Publishing, 2024)
The course begins by introducing you to Linux, the powerful operating system that powers most servers and embedded systems worldwide. We explore the significance of Linux in today's tech-driven world, highlighting its use in everything from mobile phones to supercomputers. The journey continues with a deep dive into open-source software, illustrating how it fosters innovation and collaboration in the tech community. The course focuses on the Linux family tree, detailing the relationships and differences between distributions such as Debian, Ubuntu, RHEL, and CentOS. This section is vital for understanding the landscape of Linux distributions and selecting the right one for your needs. We also cover essential considerations for selecting compatible hardware, ensuring you can build or choose a system that runs Linux flawlessly. The course wraps up with practical skills, including installing Ubuntu and CentOS, using productivity suites, and navigating the Linux filesystem. You'll learn the basics of the terminal and shell, discover how to install software across different distributions, and manage user accounts and permissions. These skills are crucial for anyone looking to thrive in a tech environment powered by Linux.
Online resource; title from title details screen (O'Reilly, viewed March 19, 2024)
Keywords: Linux; Operating systems (Computers); Systèmes d'exploitation (Ordinateurs); operating systems; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet